Vybor 2000 . Vybor 2000 . Choice 2000 . Выбор 2000 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Political game show. Featured in the program: Chuev, Aleksandr (Politician); Filin, Vladimir (Politician) Contributors: Vasil'kov, Igor' (Anchor) Политическая игра-шоу. В программе участвуют: Чуев, Александр (Политик); Филин, Владимир (Политик) Создатели: Васильков, Игорь (Ведущий/Ведущая)